Beaterios in Colonial Lima. The case of a pious noble indigenous women - Espinoza Soriano, Waldemar (2014)
The Christianization of Peru, in which the Spanish priests put a lot of care and strategies, took the sons of the Inca nobility and curacal as the main catechumens. That resulted in their children, little by little, feel attractive by the Catholic religion, to the point that many teens act out their desire to follow an ecclesiastical career. To this end, the late seventeenth century, was founded in Lima a pious for women belonging to the aristocracy of the Andes. He was called Beaterio de Nuestra Señora de Copacabana, located in the Paseo de los Descalzos. It endured many vicissitudes, but has managed to survive until today with the status of convent, dedicated to the education of girls.